The Impact of Abusive Supervision and Locus of Control on Budgetary Slack - Fitri Mareta; Aldini Nofta Martini; Aryan Danil Mirza; Elin Paulina (Future Science, 2020)
Previous research has shown that budgetary slack behavior is motivated by external factors based on employee preferences or internal factors. Abusive supervision and locus of control are two aspects that have the potential to be the cause of budgetary slack creation. This research aims to investigate the impact on the propensity of individuals (abusive supervision and locus of control) to execute budgetary slack. Furthermore, this research also explores the role of the individual locus of control through abusive oversight of the tendency to handle budgetary slack. Until now, no research has been conducted to investigate the role of the individual locus of control in reaction to abusive supervision that facilitates budgetary slack activity. This research used a 2 x 2 experimental method among 51 Master of Science in Accounting students as participants to test the hypothesis. The findings show that the tendency to create budgetary slack is not significantly influenced by abusive supervision, whereas the emphasis of regulation has a major impact on the tendency to generate budgetary slack. Furthermore, it was also found that the propensity to create budgetary slack is influenced by abusive supervision and locus of control. In an attempt to reduce employee budget discrepancies, this analysis contributes empirically and theoretically by being the framework for consideration in the company.